mRNA mediates passive vaccination against infectious agents, toxins, and tumors - Moritz Thran; Jean Mukherjee; Marion Pönisch; Katja Fiedler; Andreas Thess; Barbara L Mui; Michael J Hope; Ying K Tam; Nigel Horscroft; Regina Heidenreich; Mariola Fotin‐Mleczek; Charles B Shoemaker; et al. (EMBO Molecular Medicine)
Abstract The delivery of genetic information has emerged as a valid therapeutic approach. Various reports have demonstrated that mRNA, besides its remarkable potential as vaccine, can also promote expression without inducing an adverse immune response against the encoded protein. In the current study, we set out to explore whether our technology based on chemically unmodified mRNA is suitable for passive immunization. To this end, various antibodies using different designs were expressed and characterized in vitro and in vivo in the fields of viral infections, toxin exposure, and cancer immunotherapies. Single injections of mRNA–lipid nanoparticle (LNP) were sufficient to establish rapid, strong, and long‐lasting serum antibody titers in vivo, thereby enabling both prophylactic and therapeutic protection against lethal rabies infection or botulinum intoxication. Moreover, therapeutic mRNA‐mediated antibody expression allowed mice to survive an otherwise lethal tumor challenge. In conclusion, the present study demonstrates the utility of formulated mRNA as a potent novel technology for passive immunization.